Pembenahan Karakter Wirausahawan Indonesia Melalui Konsep Islamic Entrepreneurship - Kholiluzzair, Muhammad (IAIN Purwokerto, 2014)
The pillars that prop up the existence of nation is character the nation it self, in other hand ruin of the nations is indicated with the moving of cultural configuration and also wisdom values that are not wanted by the establisher. The Formation of Indonesia Entrepreneurship character can be done with Entrepreneurship concept that input Islamic values in the application. Beside it, character also will related to the thing that affect, the example that character is formed from environment, education or training.